The Political Economy of Farmland Taxation in Colonial and Postcolonial Zimbabwe, 1914-32 and 1980-c. 2018 - Koke, Honest Elias; Ncube, Sibanengi (African historical review, 2023)
This article contributes to the existing literature on the political economy of Zimbabwe by focusing on a hitherto understudied area, land taxation. While scholars have written extensively on the political economy of land in general, not much is available on debates around its taxation. Those that have written on the land question have paid less attention to its taxation. Similarly, recent works on the colony's fiscal system lack the scope for a detailed examination of the land taxation question. By analysing how different governments of the country operating within distinct historical contexts approached the question of land taxation reinserts land taxation in conversations around the political economy of both colonial and postcolonial Zimbabwe, particularly how politics and economics intersected in shaping policy formulation and implementation. During the colonial period, the main idea behind the imposition of land tax was to force absentee landowners and those who occupied land for speculative purposes to sell their land or develop it; however, the situation changed following the Fast Track Land Reform Programme in 2000. At that stage, the main objective for land taxation shifted from encouraging the selling of land for redistributive purposes to making resettled farmers utilise their land. In either case, land taxation and contestations around it provide another way of looking at the dynamics of state making in settler colonial and post-settler colonial contexts. The article relies on a wide range of sources that include parliamentary debates, newspapers, archival sources, and other political pamphlets and documents. A close analysis of archival sources shows how arguments for and against land taxation changed or persisted across the colonial and postcolonial historical epochs.